KAJIAN Pergerakan kendaraan belok kiri langsung dan lurus langsung pada simpang bersinyal - Abadi, Khoirul; Muryanto, Imam; Eka Wijayanti, Hermin (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
Setting the left turn movement at the intersection of four or three signalized intersections, and the straight movements at three signalized intersections. In any where, there are not provide significant for signalized intersection performance. Changes related legislation does not necessarily contribute positively to the traffic operation. Determination of the application of left turn on redÂ (LTOR) or straight on red (STOR) at an intersection must be preceded by a study, so that the positive affect or negative affect that happened can be known early. The background of this study was motivated the existing conditions arrangement, turn left movements (for intersection of four or three signalized intersections) and straight movements (for three signalized intersections) at some intersection in Malang Raya. In addition, this study was conducted in order to know the effect of setting the movement of vehicles turning left or straight at the intersection. The expected benefits of this study is, that every movement settings, turn left at the intersection of four or three signalized intersections, and also straight movements at three signalized intersections have to go through the review process. Conclusion, shows that the movement of vehicles turning left directly on the intersection of four or three signalized intersections, and the movement of vehicles at the intersection of three straight directly affect the performance of signalized intersections.Key words: signalized intersection, turn left movement, straight movement, the performance of a signalized intersection.